ANALISIS RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO PROFITABILITAS TERHADAP KINERJA KOPERASI AS-SAKINAH DI SIDOARJO TAHUN 2009-2012 - Firdaus, Filjanatul (Jurnal Akuntansi AKUNESA, 2014)
This research analyzes the performance of cooperatives As-Sakinah Sidoarjo that was based on the financial statement period 2009-2012. As for research purposes to know and analyze the performance of cooperatives As-Sakinah Sidoarjo as seen from the level of solvency ratio liquidity ratio, and the ratio of profitability in 2009-2012. The results showed that the ratio of liquidity increase this cooperation shows the ability of cooperatives to meet financial obligations at the time charged. The ratio of solvablitas cooperative quite well so that cooperatives can pay his debts when one was disbanded. Profitability ratio of cooperation has decreased, the decline in this ratio shows the cooperative should increase sales, total assets and capital in order to increase Profitability can be fulfilled.Keywords: liquidity ratios, solvency ratios, profitability ratios, performance of the cooperative.